Evaluating the Usability and Learning Impact of an Augmented Reality Application for World War II Historical Tourism Sites among Indonesian High School Students - Agung Dwi Saputro; Theonaria Kaban; Remuz Maurenz Bertho Kmurawak; Mingsep Rante Sampebua; Ishak Semuel Beno (Universitas Pendidikan Ganesha, 2025)
Education in the modern era is carried out by integrating technology to support the learning process. However, its implementation still faces several challenges, such as limited access to authentic learning resources and low student engagement due to the use of static instructional media. The developed application, BERCABAR (Belajar Cagar Budaya dengan AR), was designed using Unity 3D and Blender, combining three-dimensional models, interactive quizzes, and multimedia content accessible in offline mode. This study explores the development and effectiveness of an Augmented Reality (AR)-based learning application aimed at enhancing students’ understanding of history through interactive and contextual learning experiences. The research employed a mixed-method approach with a one-group pretest–posttest design involving secondary-level students as research participants. Quantitative data were collected through learning achievement tests and analyzed using the N-Gain test, while qualitative data were obtained through interviews and observations of user experiences. The findings revealed a significant improvement in students’ cognitive abilities, accompanied by a very high level of user satisfaction and stable system performance on mobile devices. These results affirm that the integration of AR technology has strong potential to enrich historical literacy, increase learning engagement, and offer innovative solutions for education in resource-limited environments.